PENERAPAN PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN MOTVASI DAN PRESTASI BELAJAR SISWA PADA TEMA 9 “KEKAYAAN NEGRIKU” DI KELAS IV MI AL – HIDAYAH KARANGAN DONOWARIH KEC. KARANGPLOSO KABUPATEN MALANG - Nova Hexa Minung Jamila; Muhammad Hanief; Rosichin Mansur (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbsrakLearning is a delibrate affotr that aims to focus on the intersts, characteristics, and conditions of others so that students can learn effectively and effiently. Lesning patterns carried out by students will take sereval stage namely: (1) the information stage (the stage of receiving information), (2) the transformation stage (the stage of information change), (3) the evaluation stage (the information assessment stage). Through these three stages, the level taken by students during learning is fulfilled. Than the learning model will experience a shift, between others: (1) learning is directed to encourge students to find out (not told) form various sources of information , (2) learning is directed at being able to formulate problems (ask quetions), (3) outinelearning is directed to train students to think analitytically (decision making) thingking mechanics (routine), (4) learning does the importance of collaboration and collaboration in solving problem. Keyword: Application of Tematik Learning